Grounded objects. Archaeology and speculative realism. (20th May 2016) - Edgeworth, Matt
Abstract: The philosophical movement known as speculative realism (SR) has much in common with archaeology. As well as a shared concern with objects and with time, both have orientations towards an external reality that exists (or existed) outside the domain of human knowledge. This paper explores overlaps and commonalities in these two very different types of investigation. Proceeding from an archaeological perspective, it critically assesses the relevance of some of the key ideas of SR for archaeology, while also looking at ways in which these can be challenged, honed, adapted and transformed through encounters with archaeological objects. It asks the question, what can archaeology usefully contribute to the SR project?